2018
DOI: 10.1002/jobm.201800195
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cpf1 facilitated large fragment deletion in Saccharomyces cerevisiae

Abstract: In this study, we focused on the applicability of CRISPR/Cpf1 in genome simplification of Saccharomyces cerevisiae and established a CRISPR/Cpf1 assisted method for rapid markerless large fragment deletion to facilitate laboratory evolution of geome of S. cerevisiae by rational genetic engineering. This method uses a Cpf1 expression plasmid and a crRNA array expression plasmid. The DNA fragment between two DSBs generated by CRISPR/Cpf1 can be cut off from the chromosome, along with re-ligation of the genomic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The result of this work demonstrated that Cpf1 can broaden application sphere of the genome-editing toolbox available for research of S. cerevisiae [69]. Li et al firstly used the CRISPR/Cpf1 to delete large DNA fragment (the deletion of DNA fragment of ∼38 kb between the two genes of TRM10 and REX4) in S. cerevisiae, which demonstrating that the CRISPR/Cpf1 system can be used for genome simplification of S. cerevisiae, and to facilitate the laboratory evolution of the genome of S. cerevisiae [70]. Later in the year, Dank et multiple genomic defects in aroma metabolism is generated and activated to show an aroma composition comparable to wild type levels [71].…”
Section: Synthetic Genomics and The Use Of Crispr Technology In Synthetic Genomics Of S Cerevisiaementioning
confidence: 99%
“…The result of this work demonstrated that Cpf1 can broaden application sphere of the genome-editing toolbox available for research of S. cerevisiae [69]. Li et al firstly used the CRISPR/Cpf1 to delete large DNA fragment (the deletion of DNA fragment of ∼38 kb between the two genes of TRM10 and REX4) in S. cerevisiae, which demonstrating that the CRISPR/Cpf1 system can be used for genome simplification of S. cerevisiae, and to facilitate the laboratory evolution of the genome of S. cerevisiae [70]. Later in the year, Dank et multiple genomic defects in aroma metabolism is generated and activated to show an aroma composition comparable to wild type levels [71].…”
Section: Synthetic Genomics and The Use Of Crispr Technology In Synthetic Genomics Of S Cerevisiaementioning
confidence: 99%
“…Larger chromosomal deletions (>30 kb) and chromosome fusion have been achieved in S. cerevisiae through NHEJ repair between endpoints of the DNA breaks, which can facilitate the study of gene clusters or minimal genome research, as well as the study of replication, recombination, and segregation [70,71,72]. In principle, this may open up the possibility to generate CRISPR-Cas9-induced genome rearrangements in C. albicans, in which specific whole-chromosome aneuploidies have been associated with drug resistance and/or cross-adaptation to different drugs [73].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Study of the correlation existing between large chromosomal rearrangements and virulence and drug resistance (e.g., aneuploidy and LOH in C. albicans, aneuploidy in C. neoformans) [70][71][72] Directed evolution through CRISPRguided DNA polymerase…”
Section: S Cerevisiaementioning
confidence: 99%
“…However, this approach is limited by the number of available marker-based plasmid backbones (4,(8)(9)(10)(11)(12). More recently, several successful examples have shown that several gRNAs can be expressed from a single gRNA-array, using different tricks to release the mature gRNAs (3,5,6,(13)(14)(15)(16)(17). However, complexity of these gRNA expression cassettes and their tailored sequence design may be difficult to synthesize and requires laborious and time-consuming cloning steps, therefore hindering the workflow for strain construction.…”
Section: Introductionmentioning
confidence: 99%